The sentences that create us: crafting a writer's life in prison - Meissner, Caits; Betts, Reginald Dwayne (Haymarket Books, 2022)
The Sentences That Create Us provides a roadmap for incarcerated people and their allies to have a thriving writing life behind bars — and through walls — drawing on the unique insights of over 50 justice-involved contributors and their allies to offer advice, inspiration and resources